Silver-perovskite hybrid electrocatalysts for oxygen reduction reaction in alkaline media - Wang, X.; Ge, L.; Zhu, Y.; Dai, J.; Zhou, W.; Shao, Zongping (The Electrochemical Society, Inc, 2018)
Developing a low-cost, and highly-efficient catalysts for improving oxygen reduction reaction (ORR) is imperative to the energy storage and conversion device. Here, we synthesized Ag/La0.6Sr0.4CoO3-d (Ag/LSC) composites by decorating LSC with Ag using the electroless technique. As a result, the LSC was homogenously overlaid with Ag nanoparticles. The derived Ag/LSC composites possessed a relatively higher specific surface area than pure LSC and Ag. The Co-O-Ag bonds in the composites contribute substantial electrons transferred from Ag to Co element, resulting in the unique electronic structures and strong electronic interaction between Ag and LSC. The significant improvements of ORR activity in alkaline solution at room temperature can be observed in Ag/LSC composites compared to the pure Ag and LSC. The composites with optimal Ag loading (50 wt%) showed best ORR activity among all the composites according to the half-wave potential and diffusion limiting current density. The presented strategy of silver surface modification via electroless process can provide effective routes for designing high performance metal oxide (e.g. perovskite) composite electrocatalysts.